Kekonsistenan Rasio Keuangan Dalam Memprediksi Peringkat Obligasi Antar Agen Pemeringkat (Pefindo, Moodys dan Standar & Poors) - Sari, Maylia Pramono (STIE Widya Manggala, 2008)
This papper seeks to analyze the ability and consistency of financial ratio variable in predicting bond rating by comparing several research using different bond rating as the data. The result of the empiric research comparation in this paper showed that the financial ratio from the financial report could describe and could be a prediction device of the company’s bond rating issued by the security rating determiner agent. In addition, it was obtained that from several agents, such as PEFINDO, Moody’s Standard & Poor’s, are all consistent. There are also some different significant variable on the previous research, it was caused by sample, period, and statistical technique used. Beside that there are still another variables used in Indonesia refered to several previous researches apart from the variable used the paper. From the conclusion’s result, there are found some variable used in forming prediction model in bond rate in Indonesia for future. Other financial ratio variables may be used for example, financialratio and size and growth of the company. Meanwhile another financial ratio variable may be used in forming the model of increasing bond. Those variables are: indenture provision (sinking fund and bond asset) and another environment factor, so that the result of the following researches about the prediction will be more accurate.